German companies relaxed about Brexit - Michael Grömling; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2017)
The United Kingdom intends to leave the single market, yet still wants to retain broad access to it by means of a comprehensive free trade agreement. But the question remains as to whether the European Union is prepared to play ball. Brexiteers claim that German companies in particular, worried about their exports to the UK, will push for a gentle compromise in the favour of the UK, so that trade can continue with as little disruption as possible. Yet a survey by the Cologne Institute for Economic Research (IW Köln) has cast doubt on this view.
Keywords: 330